Heinle & Heinle Toefl Test Assistant : - Broukal, Milada (Heinle & Heinle Publishers, 1995)
This text - part of a five-text series - prepares students for the Structure and Written Expression section of the TOEFL as well as the grammar sections of the Listening Comprehension and Reading sections of the TOEFL.